Locke’s Epistemological Anthropocentrism (in Polish) - Misztal, Dawid (Diametros, 2013)
Reading Locke’s philosophy mainly as criticism of the Cartesian innatism results in disguising its tensions and motives. Although the article is not completely free of this popular strategy of interpretation, it aims at avoiding its simplifications. This allows to show the complexity of the relation of Locke’s philosophy to the fundamental ideas of innatism and to bring out contradictory interests he hopes to reconcile.